Christmas Program at Jackson Elementary School - Watkins, Howard::::::::: (1984)
1st grade class singing on stage; "reindeer "boys in front: 1st row: #3 Adam Watkins; 3rd row #1 Jimmy To other "reindeer "boys also walking off stage